Emergence of the Tyndale–King James Version tradition in English Bible translation - Naudé, Jacobus A. (AOSIS Publishing, 2022)
In this essay, it is demonstrated that the inception of the English Bible tradition began with the oral–aural Bible in Old English translated from Latin incipient texts and emerged through a continuous tradition of revision and retranslation in interaction with contemporary social reality. Each subsequent translation achieved a more complex state by adapting to the emergence of incipient text knowledge (rediscovery of Hebrew and Greek texts), emergence of the (meaning-making) knowledge of the incipient languages (Latin, Hebrew and Greek), language change (Old, Middle and Modern English), mode of communication (hearing-dominant and text-dominant), style (literal or word-for-word) and products (oral-aural Bible, handwritten manuscript Bible and printed Bible). Historical sources indicate that there were translations of portions of the English Bible since 700 CE as handwritten manuscript Bibles in Old and Middle English and in print in Modern English – even before the retranslation associated with Tyndale (1526) and despite ecclesiastical opposition since 1408. This version and its revisions (1530–1531, 1534) are followed by subsequent revisions (Coverdale Bible, Matthew’s Bible, Great Bible, Geneva Bible and Bishop’s Bible). The next revision was the King James Version (1611), which replaced all its predecessors, and which was never replaced for the next four centuries – not even by its revisions. 𝗖𝗼𝗻𝘁𝗿𝗶𝗯𝘂𝘁𝗶𝗼𝗻: Contrary to the fragmentation caused by ordering individual English Bibles either by period (e.g. 20th century) or according to their features (e.g. literal), it is demonstrated that the history of English Bible translation emerged rather as a translation complex, and its history must be understood in this way.
Keywords: King James Version; Tyndale Bible; Geneva Bible; Bishops’ Bible; Great Bible; Matthew’s Bible; Coverdale Bible; American Standard Version